2014
DOI: 10.1021/ma5009226
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Intrinsically Ultramicroporous Polyimides Containing Bridgehead-Substituted Triptycene for Highly Selective and Permeable Gas Separation Membranes

Abstract: Highly ultramicroporous, solution-processable polyimides bearing 9,10-bridgehead-substituted triptycene demonstrated the highest BET surface area reported for polyimides (840 m 2 g −1 ) and several new highs in gas selectivity and permeability for hydrogen (1630−3980 barrers, H 2 /CH 4 ∼ 38) and air (230−630 barrers, O 2 /N 2 = 5.5−5.9) separations. Two new dianhydrides bearing 9,10-diethyl-and 9,10-dipropyltriptycenes indicate that the ultramicroporosity is optimized for fast polymeric sieving with the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
168
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(185 citation statements)
references
References 53 publications
14
168
0
Order By: Relevance
“…The systematic increase in free volume and narrow microporosity correlates well with the reduction in backbone torsional freedoms going from 6FDA to SPDA to TPDA, which inhibits efficient chain packing. This increased intra-chain rigidity is also consistent with the report of a 50% higher Young's modulus for KAUST-PI-1 (2460 MPa) relative to PIM-PI-1 (1620 MPa) [37]. …”
Section: Microstructural Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The systematic increase in free volume and narrow microporosity correlates well with the reduction in backbone torsional freedoms going from 6FDA to SPDA to TPDA, which inhibits efficient chain packing. This increased intra-chain rigidity is also consistent with the report of a 50% higher Young's modulus for KAUST-PI-1 (2460 MPa) relative to PIM-PI-1 (1620 MPa) [37]. …”
Section: Microstructural Analysissupporting
confidence: 90%
“…That is, replacing the spirobisindane contortion centers (single tetrahedral carbon atom shared by two rings) of the earliest reported solution-processable ladder PIMs [20,30,31] and PIMPIs [17,23,32,33] with bridged bicyclics (e.g., ethanoanthracene [34], Tröger's base [35,36], and triptycene [18,19,21,37]) enhanced the polymer intra-chain rigidity to simultaneously boost permeability and selectivity. For example, replacing only the relatively flexible spirobisindane (SPDA) contortion center of PIM-PI-1 with a shapepersistent 9,10-diisopropyltriptycene (TPDA) moiety (i.e., KAUST-PI-1) and barring any other changes in the backbone ( [19].…”
Section: Introductionmentioning
confidence: 99%
“…Non-equilibrium excess free volume resulting from casting procedures or methanol treatment is dissipated and large reductions in permeability along with increases in selectivity are often reported. Our group has previously demonstrated that thick films (~70-100 µm) undergo a rapid aging phase until an "aging knee" around 10-15 days at which quasi-steady-state transport properties may be observed even until 150 days [23]. Accordingly, 6FDA-DAT1 and 6FDA-DAT2 were aged for 150 days and their resulting pure-gas permeabilities and ideal selectivities are reported in Table 2.…”
Section: Pure-and Mixed-gas Co 2 /Ch 4 Permeation Properties After Phmentioning
confidence: 99%
“…One class of PIMs is based on high-free-volume aromatic polyimides (PIM-PIs) that contain rigid contortion sites either in their dianhydride and/or diamine moiety. Examples of such molecular building blocks are: (i) spirobisindane dianhydrides [7,12,13] and diamines [14,15], ethanoanthracene dianhydride [6,16], spirobifluororene dianhydride [17] and diamines [18,19], Tröger's base diamines [20][21][22], and triptycene dianhydrides [10,23] and diamines [15,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…PIM-1 is a widely studied candidate in the class of PIMs due to its rigid and contorted structure. 9 Since then, several examples of PIMs containing units such as triptycene, 10,11 spirobisindane, 12,13 Tr€ oger's base, [14][15][16][17] spirobischromane, 18 spirobifluorene, 19 hexaphenylbenzene, 20 naphthalene, 21 tetraphenylethylene, 22 phthalimide, 23 tribenzotriquinacene, 24 cardo PIMs, and so on 25 have been synthesized and evaluated as membrane materials for gas separation.…”
mentioning
confidence: 99%